Lactobacillus and Bifidobacterium Bacteria Profile in Healthy People and People with Type 2 Diabetes Mellitus - Rizki Nurmalya Kardina; Kartika Yuliani; Farah Nuriannisa (State Islamic University of Sunan Ampel, 2021)
Lactobacillus and Bifidobacterium are two genera of gram-positive bacteria that are widely used as probiotic products to improve the composition of the intestinal microbiota but until now the difference in the number of these bacteria in patients with type 2 diabetes mellitus and healthy people in Asia remains unclear. This study conducted a systematic review to analyze the differences in the number of Lactobacillus and Bifidobacterium bacteria in patients with type 2 diabetes and healthy people in Asia. The results showed that the number of Lactobacillus bacteria was higher in patients with type 2 diabetics than in healthy people. The number of Bifidobacterium bacteria in patients with type 2 diabetes tended to be lower than in healthy people, although there was some literature stating that there was no difference in the number of Bifidobacterium bacteria in patients with type 2 diabetes and in healthy people. Further research on the profile of Lactobacillus and Bifidobacterium bacteria per type (species) specifically in people with type 2 diabetes and healthy people of various ethnicities in Indonesia is needed to identify dysbiosis in people with type 2 diabetes and determine specific microbiota therapy for people with type 2 diabetes.